Estudo experimental sobre a resposta imunológica em infecções seqüenciais pelo vírus Dengue 3 e pelo vírus Dengue 2 em primatas não humanos da espécie Callithrix penicillata - FERREIRA, Milene Silveira (Universidade Federal do Pará, 2015)
Dengue fever is caused by Dengue virus (DENV - Flaviviridae, Flavivirus) and is considered the most widespread arbovirus in the world. Currently, there is an animal that fits a model for studies on the pathogenesis of DENV. To investigate the susceptibility of the DENV Callithrix penicillata were inoculated samples DENV-3 and DENV-2 isolated from human cases of fatal. To do this, twenty-two animals were infected with DENV-3 (3.23 × 103 PFU/mL) and sixty days after infection (dai), 11 of these were secondarily infected with DENV-2 (4.47 × 104 PFU/mL). Blood, plasma and serum were collected daily during the first seven days and for 15, 20, 45, and 60 dai. We investigated the production of IgM antibodies and inhibitors of hemagglutination (HI), as setup were analyzed biochemical and hematological profile and serum cytokine levels (IL-6, TNF- α, IL-2, IFN-, IL-4 and IL-5). Primary infection (DENV-3) showed IgM (15-20 dai), antibodies IH (15-60 dai), increased levels of TNF-α and IFN-γ and decreased IL-5. In secondary infection (DENV-2) was detected IgM antibodies (15-20 dai), antibodies HI (15-60 dai), and decreased levels of IL-6, TNF-α, IFN-γ and IL-5. Furthermore, it was observed in both infections leukopenia, neutropenia, lymphocytopenia, monocytopenia, thrombocytopenia, and increased AST. The high levels of INF-γ and TNF-α showed activation of the inflammatory response, as the response to cellular differentiation and suppression of proliferation of cytokine features of the humoral response. The presence of neutralizing antibodies may have caused suppression of the inflammatory response in secondary infection which may have led to the absence of signs of Dengue Hemorrhagic Fever/Dengue Shock Syndrome (DHF/DSS) during secondary infection (DENV-2). The results indicate that non-human primates Callithrix penicillata demonstrated susceptibility to DENV strains of human origin, suggesting that these animals are a good model for studies of the immune response of Dengue Fever (DF) and for the assessment of a tetravalent vaccine.